Impact of Telemedicine on Hospital Financial Models - Susanti, Rini; Syarkani, Yofi; Ratna Sari Handayani, Dwi; Waluyo, Imam (Jurnal Multidisiplin Indonesia, 2025)
Telemedicine has emerged as a transformative solution to enhance healthcare accessibility and efficiency, especially during the COVID-19 pandemic. Despite its benefits, its adoption and sustainability face significant barriers, including high initial costs, inconsistent reimbursement policies, digital divides, and operational challenges. These issues disproportionately affect rural and underserved populations, limiting equitable access and efficiency in healthcare delivery. This study aims to assess the financial and operational impacts of telemedicine, with a particular focus on hybrid telehealth models that integrate virtual consultations with in-person care. It investigates the role of government subsidies in addressing financial barriers and ensuring long-term sustainability. Telemedicine improves healthcare accessibility but faces economic, technological, and social barriers. Future research must explore underserved areas, hybrid models, and digital literacy, while policymakers should enhance infrastructure and implement inclusive policies. The study underscores the transformative potential of telemedicine in reshaping hospital financial models while promoting equitable access to care. It highlights the necessity for targeted strategies and government support to overcome existing barriers, ensuring that telemedicine serves as an effective and inclusive healthcare solution. Future efforts should focus on optimizing subsidy allocation to maximize both economic and healthcare benefits.